An Experimental Study on Boron Carbide Reinforced Open Cell Aluminum Foams Produced via Infiltration Technique - Sunar, T.; Cetin, M. (Engineering, Technology & Applied Science Research, 2018)
Light structures and parts are very effective for new engineering applications. Their considerably low densities, high energy absorption capabilities, and desirable mechanical properties make them useful for particularly automotive, defense and aerospace industries. Besides these positive properties, it is known that the production and processing of cellular materials is very tough and worth the effort. Recently, with advances in new technologies like 3D printing or selective laser melting, now different types of cellular materials can be produced. But manufacturing of metallic foams via casting especially replication or infiltration method is fairly an economic method when compared with other methods. In this study, vacuum-gas infiltration set-up was used to produce B4C reinforced aluminum foams. The mentioned method involves the addition of space holder materials and a dissolution technique to remove them after solidification of the metal. As space holder materials NaCl particles were selected and mixed with B4C powders to produce B4C reinforced A360 aluminum foam. By changing the weight ratio of B4C particles, the alteration of properties like porosity, compression strength, and energy absorption capacity was investigated. Additionally, computer tomography views were obtained to see and interpret the microstructures of the foams. Compression tests were carried out to evaluate the mechanical behavior of the foams under static loading. The porosities of samples obtained as between 65-75%. The compressive strength increased with rising relative density.